Data on the first experience of insulin degludec (Tresiba®) treatment for type 2 diabetes in daily clinical practice - Lyudmila Alexandrovna Suplotova (Endocrinology Research Centre, 2015)
Aim: The aim of this study was to evaluate the efficacy and safety of the new ultra-long-acting insulin degludec (Tresiba®) in the treatment of type 2 diabetes in routine clinical practice.Methods: This primary health care clinical observational study included 20 insulin-naïve type 2 diabetic patients (mean age: 57.2 years, range: 54.4–61.5 years), who were inadequately controlled on maximum tolerated doses of oral antidiabetic drugs (OADs) and in whom baseline insulin therapy with ultra-long-acting insulin degludec was initiated. The duration of treatment was 6 months. The list of procedures met the ‘Standard of primary medical care in non-insulin-dependent diabetes mellitus’, as approved by the Ministry of Health of the Russian Federation (12.28.2012 №1581-n). Quality of life was assessed using the SF-36 questionnaire. All patients provided written consent before participating in the study.Results: In the outpatient setting, insulin degludec was well tolerated by all the patients. During the observational period, there were no events of symptomatic hypoglycaemia confirmed by self-measured plasma glucose (blood glucose level <3.9 mmol/l). At the end of the observational period, HbA1c, fasting plasma glucose level (FPG) and postprandial (2 h after a meal) plasma glucose level (PPG) had decreased. Despite the fact that most of the patients had poor baseline glycaemic control, after 6 months of degludec therapy, 45% of the participants achieved a target HbA1c of <7.0%, and 45% achieved a target HbA1c of <8.0%. Improved glycaemic control was associated with increased quality of life scores on both physical and mental health components.Conclusion: In this primary health care clinical observational study, the initiation of insulin degludec in type 2 diabetes patients with poor glycaemic control on OADs was associated with the achievement of effective glycaemic control. In addition, it had a good safety profile, and it improved quality of life scores and adherence to the treatment.